Pengaruh Laju Sedimentasi terhadap Kapasitas Tampung Danau Sentarum, Provinsi Kalimantan Barat - M. Ma'ruf Akafi; Albert Wicaksono (JURNAL SUMBER DAYA AIR, 2025)
Lake Sentarum has a unique role as flood control in the lower reaches of the Kapuas River Basin. Changes in land use and high rainfall can cause an increase in the rate of erosion and sedimentation that occurs in the Sentarum Sub-river basin, which potentially reduces the storage capacity of Lake Sentarum. The objective of this study is to determine the sedimentation rate and analyze the impact of sedimentation on the storage capacity of Lake Sentarum.The erosion rate analysis using the Universal Soil Loss Equation (USLE) method shows that in the 2015 to 2020 period, the most significant erosion rate occurred in 2016,which 2016 was the year with the highest rainfall. The erosion rate that occurred in 2016 in the Sentarum Sub-river basin and Lake Sentarum catchment area was 293,622.79 Ton/Ha/year and 160,413.01 Ton/Ha/year, respectively. The types of land cover that have the most impact on erosion rates are dryland agriculture mixed with shrubs, plantations, shrubs, and open land. The sedimentation rate was calculated using the Sediment Delivery Ratio (SDR) method, where the most significant sedimentation rate occurred in 2016 with the sedimentation rate of the Sentarum Sub-river basin was 201.842,37 Ton/Year which resulted 86.702,05 m3 of sediment volume and the Lake Sentarum catchment sedimentation rate was 117.591,64 Ton/Year which resulted in 50.511,87 m3 of sediment volume. With an average sediment volume in the Lake Sentarum catchment from 2015 to 2020 of 42,668.05 m3, Lake Sentarum will lose its capacity by 0.001% each year.